Economía ecológica, economía solidaria y sustentabilidad: Elementos conceptuales - Almeida Guzmán, Marcia (2023)
The purpose of this document is to provide an overview of the interactions between the economy, environment and environmental sustainability, essential for a diverse country like Ecuador, historically both their participation in worid trade as its own intemal operation is based on a primary export model with a very high environmental cosí, so now it is essential to reconcile development with ecology resulting in strategies leading to sustainable development. The document through bibliographic searches raise concems arguments that area framework for future applied research and reflections on this important issue of local and global impact.